Maternity & women's health care - Lowdermilk, Deitra Leonard (St. Louis, Missouri : Elsevier, 2020)
Provides evidence-based coverage of everything you need to know about caring for women of childbearing age. In describing the continuum of care, this title integrates the importance of understanding family, culture, and community-based care.
21st Century Maternity and Women's Health Nursing -- The Family and Culture -- Nursing and Genomics -- Assessment and Health Promotion -- Violence Against Women -- Reproductive System Concerns -- Sexually Transmitted and Other Infections -- Contraception and Abortion -- Infertility -- Problems of the Breast -- Structural Disorders and Neoplasms of the Reproductive System -- Conception and Fetal Development -- Anatomy and Physiology of Pregnancy -- Nursing Care of the Family During Pregnancy -- Maternal and Fetal Nutrition -- Labor and Birth Processes -- Maximizing Comfort For The Laboring Woman -- Fetal Assessment During Labor -- Nursing Care of the Family During Labor and Birth -- Postpartum Physiologic Changes -- Nursing Care of the Family During the Postpartum Period -- Transition to Parenthood -- Physiologic and Behavioral Adaptations of the Newborn -- Nursing Care of the Newborn and Family -- Newborn Nutrition and Feeding -- Assessment of High Risk Pregnancy -- Hypertensive Disorders -- Hemorrhagic Disorders -- Endocrine and Metabolic Disorders -- Medical-Surgical Disorders -- Mental Health Disorders and Substance Abuse -- Labor and Birth Complications -- Postpartum Complications -- Nursing Care of the High-Risk Newborn -- Acquired Problems of the Newborn -- Hemolytic Disorders and Congenital Anomalies -- Perinatal Loss, Bereavement, and Grief.
Includes bibliographical references and index.
Keywords: Maternal-child nursing; Genital diseases, Female -- Nursing; Neonatal nursing -- Methods; Obstetrical nursing -- Methods; Pregnancy complications -- Nursing; Women's health